PENINGKATAN PENGETAHUAN DAN SIKAP KADER POSYANDU TENTANG STANDAR MENU PMT BERBASIS PANGAN LOKAL MELALUI PENYULUHAN DI WILAYAH KERJA UPTD PUSKESMAS RANTO PEUREULAK ACEH TIMUR - Agnes Sry Vera Nababan; Rosa Putri; Wanda Lestari; Athira Demitri (STIKES Columbia Asia Medan, 2024)
Providing Supplementary Food (PMT) made from local food is one of the strategies for dealing with nutritional problems in toddlers and pregnant women. The availability of various food ingredients has not been utilized optimally as the basic ingredients for Supplementary Food, this is due to the lack of understanding and application of local food-based PMT menu standards by local Posyandu cadres who are the frontline health workers and services to provide education and understanding to mothers of toddlers. This study aims to determine the increase in knowledge and attitudes of Posyandu cadres about local food-based PMT menu standards through counseling. The type of research is Pre-Experimental with a One Group Pre Test and Post Test Design. The research sample consisted of 59 Posyandu cadres in the UPTD Ranto Peureulak Health Center Work Area, East Aceh. Data were analyzed by conducting a Paired T-test analysis test. Results; The results of the study showed a significant value of knowledge p value (0.000), attitude p value (0.000). Conclusion; There is an influence of counseling on increasing the knowledge and attitudes of Posyandu cadres about the standard PMT menu based on local food in the Working Area of ​​UPTD Puskesmas Ranto Peureulak East Aceh. Posyandu cadres are expected to make full use of educational media such as leaflets, which have been provided in the counseling. Reading and referring back to this material regularly can help strengthen knowledge and positive attitudes towards the standard PMT menu based on local food.